Dual-tracer 18F-FDG and 18F-AlF-NOTA-octreotide PET/CT imaging in oncocytic thyroid adenoma: a case report and literature review - Li, Jing (Frontiers in Endocrinology, 2025)
Introductiononcocytic thyroid adenoma (OA), a rare benign neoplasm, poses diagnostic challenges in conventional imaging modalities. The study investigates the diagnostic utility of dual-tracer 18F-fluorodeoxyglucose (18F-FDG) and 18F-AlF-NOTA-octreotide (18F-OC) positron emission tomography/computed tomography (PET/CT) in characterizing OA.MethodsWe present a histopathologically confirmed OA case evaluated through simultaneous 18F-FDG and 18F-OC PET/CT imaging. Quantitative analysis included maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), and metabolic tumor volume (MTV). A systematic literature review was conducted to contextualize the imaging findings within existing evidence.ResultsA 44-year-old female presenting with ACTH-independent Cushing syndrome (morning cortisol 632.8 nmol/L, non-suppressed on dexamethasone suppression tests) underwent comprehensive endocrine evaluation. Incidentally detected thyroid nodule demonstrated discordant tracer uptake: 18F-FDG PET/CT revealed intense hypermetabolism (SUVmax=31.68; SUVmean=9.18; MTV=4.33 cm3), while 18F-OC PET/CT showed moderate uptake (SUVmax=6.86; SUVmean=4.41; MTV=1.72 cm3). Histopathology confirmed OA with negative SSTR2 expression. Postoperative cortisol levels remained elevated. After nearly two years of clinical follow-up with conservative management using symptomatic medication, she underwent pituitary lesion resection, which confirmed a pituitary adenoma/pituitary neuroendocrine tumor (PitNET) consistent with a densely granulated corticotroph tumor.ConclusionThis case demonstrates the complementary diagnostic value of dual-tracer PET/CT in OA characterization, particularly in SSTR2-negative variants. The discordant uptake patterns suggest distinct metabolic pathways in OA pathophysiology. Prospective multicenter studies with larger cohorts are warranted to establish standardized diagnostic criteria and explore theranostic applications of these imaging biomarkers in OA.